Akreditasi Sekolah Atau Madrasah Dalam Meningkatkan Mutu Pendidikan Islam - Suharsono; Purwaningsih, Fajar; Sirojuddin, Wildan (STAI Yogyakarta, 2024)
School accreditation is an effort to guarantee school quality and an effort to achieve the expected quality of education and the results are realized in the form of recognition and suitability rankings issued by the National School/Madrasah Accreditation Board. This research aims to determine and describe the implementation of school accreditation in improving the quality of education in Islamic Education Institutions by using school accreditation mechanisms and accreditation components. This research method uses library research methods which are related to library data collection methods. The data collection technique in this research uses documentation and the data analysis technique for this research uses critical analysis, where this analysis is critical in nature, generally based on views or values. certain things that the researcher believes are related to the problem of improving the quality of education through documents related to the problem that the researcher is studying. The results of this research are that accreditation is an effort to improve the quality of education in educational units. One of the objectives of implementing accreditation is to map the quality of education based on the National Education Standards (SNP) which consists of 8 SNPs so that there is unity and equality of education throughout the territory of the Republic of Indonesia. By implementing the accreditation concept, education quality mapping and education quality improvement plans can be carried out.